r 2004
DOI: 10.20955/r.86.41
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Effects of Monetary Policy in the United States

Abstract: We also consider asymmetric effects that are implied by models with menu costs (see, among others, Romer, 1990, andMankiw, 1994). In static (deterministic) settings, standard menu-cost models imply that "big" monetary policy shocks are neutral because firms would find it optimal to adjust nominal prices, while "small" monetary policy shocks would have real effects because keeping nominal prices fixed is associated with only a second-order cost. In other words, the firms have to decide-before the monetary polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
44
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 53 publications
7
44
0
3
Order By: Relevance
“…This asymmetry -which is also predicted by our model (as shown below) -is further documented by a large body of empirical literature that explicitly focuses on output. For example, DeLong andSummers (1988), Cover (1992), Thoma (1994), and Ravn and Sola (2004) show for the United States that positive changes in the rate of money growth induce much weaker output reductions than negative changes in the rate of money supply. Morgan (1993) and Ravn and Sola (2004) confirm this asymmetry, when monetary policy is conducted via changes in the federal funds rate.…”
Section: Relation To the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…This asymmetry -which is also predicted by our model (as shown below) -is further documented by a large body of empirical literature that explicitly focuses on output. For example, DeLong andSummers (1988), Cover (1992), Thoma (1994), and Ravn and Sola (2004) show for the United States that positive changes in the rate of money growth induce much weaker output reductions than negative changes in the rate of money supply. Morgan (1993) and Ravn and Sola (2004) confirm this asymmetry, when monetary policy is conducted via changes in the federal funds rate.…”
Section: Relation To the Literaturementioning
confidence: 99%
“…For example, DeLong andSummers (1988), Cover (1992), Thoma (1994), and Ravn and Sola (2004) show for the United States that positive changes in the rate of money growth induce much weaker output reductions than negative changes in the rate of money supply. Morgan (1993) and Ravn and Sola (2004) confirm this asymmetry, when monetary policy is conducted via changes in the federal funds rate. Additional evidence is provided by Tan et al (2010) for Indonesia, Malaysia, the Philippines, and Thailand and by Mehrara and Karsalari (2011) for Iran.…”
Section: Relation To the Literaturementioning
confidence: 99%
“…The second feature connects to a growing body of empirical evidence suggests that typical macroeconomic shocks-such as oil prices, government spending, or nominal aggregate demand-have nonlinear effects on the economy [for example, DeLong and Summers (1988), Cover (1992), Hooker and Knetter (1996), Hooker (2002), Ravn and Sola (2004), Choi and Devereux (2005), Cologni and Manera (2006)]. Some asymmetric effects have been attributed to nonlinearities in the structure of the economy, 2 Some work examines one-time, permanent endogenous regime changes [for example, Sims (1997), Daniel (2003), and Mackowiak (2006)].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, including Weise (1999), Ravn and Sola (2004), have found that the response of output (and hence income) is asymmetric in monetary expansions and contractions. Rothman (1991), and Skalin and Terrasvirta (2002) have documented asymmetries in U.S. ISSN 1948-5433 2013 unemployment rates, while Rahman and Serletis (2010) find that oil price shocks have asymmetric effects on macroeconomic variables.…”
Section: Research In Applied Economicsmentioning
confidence: 99%